Ethiopia : Staff Report for the 2002 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses Ethiopia's 2002 Article IV Consultation and Third Review Under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Performance under the first annual PRGF-supported program was good, and the second annual program remains on track. All the quantitative and structural performance criteria and benchmarks for December 2001 and March 2002 were met, with the exception of the revised regulation for the provisioning by banks for nonperforming loans, which was adopted, but was not fully in line with international best practice, as had been envisaged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet